2004
DOI: 10.1111/j.1600-0722.2004.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Undermining of enamel as a mechanism of abfraction lesion formation: a finite element study

Abstract: Many workers have suggested that abfraction lesion formation is caused by the physical overloading of enamel. However, an alternative mechanism, involving undermining of the cervical enamel along the amelodentinal junction (ADJ), may be a more realistic explanation. The aim of this study was to examine what effect undermining of the buccal cervical enamel would have on the stress distribution in upper teeth. Two-dimensional plain strain finite element meshes of an upper incisor, canine and first premolar and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 25 publications
(29 reference statements)
2
60
1
14
Order By: Relevance
“…Contrary to our results, Rees et al 4,14,[33][34][35] proposed that the sampling horizontal planes were chosen at 1.1 ㎜ above the CEJ among the buccal cervical region because an initial pilot study showed this to be the position of maximum stress concentration. Despite their findings, the results of their study must be interpreted with a certain amount of caution.…”
Section: ⅳ Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Contrary to our results, Rees et al 4,14,[33][34][35] proposed that the sampling horizontal planes were chosen at 1.1 ㎜ above the CEJ among the buccal cervical region because an initial pilot study showed this to be the position of maximum stress concentration. Despite their findings, the results of their study must be interpreted with a certain amount of caution.…”
Section: ⅳ Discussioncontrasting
confidence: 47%
“…More recently, an additional mechanism for cervical tooth loss with occlusal loading has been proposed 2,4) . Grippo 3) has coined the term "abfraction" to distinguish it from lesions caused by erosion and abrasion.…”
Section: Effects Of Occlusal Load On the Cervical Stress Distributionmentioning
confidence: 99%
“…It is a general rule of engineering that stress will always follow the path of the stiffest material, that is, the path with the highest elastic modulus. In the case of an intact tooth, the stiffest material is the enamel, and an applied occlusal load is generally passed through the enamel and into the underlying dentine, with the load being dissipated through the crown and down into the root in a radial and apical direction 28) . Therefore, strictly from a mechanical point of view, it can be said that the best approach is to apply restorative materials with high Young' s modulus as possible.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…A direct, quantitative comparison between the stresses generated by these techniques has been made. Two-dimensional axisymmetric finite element modeling has been used in most previous research 22,23,28) . Although numerical results can be easily obtained in two dimensional modeling, it has some significant shortcomings.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…More recently, an additional mechanism for cervical tooth loss that links with occlusal loading has been proposed 2,3,5,7) . There is some clinical evidence for the association of abfraction lesions with heavy occlusal loads.…”
Section: Effects Of Occlusal Load On the Stress Distribution Of Four mentioning
confidence: 99%